PENGARUH INSENTIF PAJAK, FINANCIAL DISTRESS, EARNING PRESSURE TERHADAP KONSERVATISME AKUNTANSI - Stefany Rina; Listya Sugiyarti (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2020)
The influence of the independent variables on the dependent variable in this study uses secondary data in the form of financial statement data on manufacturing companies in the consumer goods industry sub-sector listed on the Indonesia Stock Exchange in 2013-2017. The research method used is quantitative. The sample used in this study amounted to 19 companies manufacturing the consumer goods industry sub-sector with a research observation period of 5 years and obtained a total final sample that can be processed as many as 95 financial statement data. Data analysis techniques used multiple linear regression with statistical tests and the operation of SPSS software version 24. The results of the study showed that tax incentives affect accounting conservatism, financial distress influences accounting conservatism while earning pressure does not affect accounting conservatism. Keywords: accounting conservatism, earning pressure, financial distress, tax incentive.